A national hospital-based survey of snakes responsible for bites in Thailand. - Viravan, C; Looareesuwan, S; Kosakarn, W; Wuthiekanun, V; McCarthy, C; Stimson, A; Bunnag, D; Harinasuta, T; Warrell, D (1992)
Snakes which had been killed and brought to hospital with the patients they had bitten were collected in 80 district and provincial hospitals throughout 67 provinces in Thailand in order to establish the geographical distribution and relative medical importance of the venomous species. Of the 1631 snakes collected, 1145 were venomous: Malayan pit vipers (Calloselasma rhodostoma), green pit vipers (Trimeresurus albolabris) and Russell's vipers (Daboia russelii) were the most numerous, while T. albolabris, C. rhodostoma and spitting cobras ('Naja atra') were the most widely distributed. In 22 cases, non-venomous species were mistaken for venomous ones and antivenom was used unnecessarily. The Malayan krait (Bungarus candidus) was confused with B. fasciatus in 5 cases and B. fasciatus antivenom was used inappropriately. The study extended the known ranges of most of the medically-important venomous species in Thailand. Correct identification of venomous snakes is especially important in Thailand because the locally-produced antivenoms are monospecific. The technique of hospital-based collection, labelling and preservation of dead snakes brought by bitten patients is recommended when rapid assessment of a country's medically important herpetofauna is required.